(untitled) (Journal of Social Sciences Review, 2024)
This study explores the transitivity patterns in academic writing of English native and Pakistani non-native students by analyzing the process types from a functional point of view based on Halliday’s (1985) framework of Systemic Functional Linguistics (SFL). The research describes and compares the process types used by English native and non-native students to transmit their experiences/ideations and fulfill intended purposes. A corpus of research articles written by English native and Pakistani non-native students was compiled and analyzed in terms of clauses and process types (material, mental, relational, verbal, existential, and behavior. The analysis reveals that both student groups prioritize material and relational processes, focusing on physical actions and linking them to associated actors with corresponding qualities. However, the subsequent processes show differences between the two groups. In the native research article corpus (NRAC), verbal, mental, and existential processes are prominent, while in the non-native research article corpus (NNRAC), mental, existential, and verbal processes prevail. Behavior processes are less frequently used in both corpora, indicating a minimal focus on physiological responses. Variation in process type rates reflects students’ choices for conveying experiences. This study contributes to understanding how linguistic choices in research articles vary between native and non-native students, shedding light on differences in communication strategies and rhetorical approaches within academic discourse.